2019
DOI: 10.1111/sms.13549
|View full text |Cite
|
Sign up to set email alerts
|

Predicting post‐operative functional ability from pre‐operative measures in ACL‐injured individuals

Abstract: Funding informationGigtforeningen; Lundbeckfonden; Aase og Ejnar Danielsens Fond; Natural Sciences and Engineering Research Council of Canada Purpose: This study aimed to quantify the relationship between objective and subjective measures of functional ability and determine if measures in the deficient (ACLd) state were correlated to, and capable of predicting a patient's objective and subjective measures in the reconstructed (ACLr) state. Methods: Twenty ACL-injured participants completed hop and side cut mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Pre- and postoperative CT- or MR-data of the donor sites could be used to more precisely and objectively reflect the comorbidity after DCIA graft harvest. This method is already frequently used in sports medicine to enable functional and anatomical comparisons and should be considered in future studies [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pre- and postoperative CT- or MR-data of the donor sites could be used to more precisely and objectively reflect the comorbidity after DCIA graft harvest. This method is already frequently used in sports medicine to enable functional and anatomical comparisons and should be considered in future studies [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for preoperative IKDC scores, the CB group had statistically significant better scores; however, their associated values were still limited with AUCs <0.65. Smale et al 16 similarly noted that subjective preoperative PRO scores are poor predictors of the postoperative condition, but further suggested that objective preoperative outcomes, such as peak knee flexion, peak knee extensor moment, stiffness, knee joint center excursion, and knee joint center boundary, have better correlations with postoperative function.…”
Section: Discussionmentioning
confidence: 99%